Social Media, Shifting Religious Authority, and Contemporary Da’wah in “Post-Secular” Indonesia - Damanhuri; Noffiyanti; Putra, Andi Eka (IAIN PONOROGO, 2025)
This paper’s point of departure is the fact that while the “secularization thesis” has been academically swept away and religion has uninterruptedly been occupying modern public sphere, on the one hand; and the emergence of new media undoubtedly paves the way for various religious expressions, on the other hand; few muslims are fully aware regarding another contemporary religious challenge they have to critically as well as emphatically engage with: a shifting religious authority. In recent years, ulama, kiai, ustadz, or ajengan—to mention just few “old” or traditional religious authorities—should share their authorities with “new” religious authorities with their far-reaching new media they effectively use—Youtube, Podcast, X, Facebook, or Instagram. With respect to certain religious controversies, religious authority is consequently highly contested between those with religious intellectual expertise and “lay” people merely well-trained with excellent command in using new media. In this respect, this paper makes a case that contemporary da’wah should necessarily be equipped with a sophisticated and far-reaching approach derived from a kind of cosmopolitan Islamic worldview through which a pluriversal and peaceful coexistence would possibly prevail. Drawing on progressively more critical and non-essentialist scholarly works and employing decolonial perspective as its theoretical framework as well as critical discourse analysis (CDA) as its method of analysis, this paper seeks to address and sheds its light on the following main questions: how do new media both simultaneously facilitate and posit a critical challenge for contemporary da’wah; and how is cosmopolitan religious consciousness incorporated and nurtured within a pluriversal society and in an era of—what Jurgen Habermas aptly coins as—post-secular age? Against the backdrop of above-mentioned media disruption and undeniable Indonesian socio-cultural pluriversality, this paper contends, a “Cosmopolitan Da’wah” is not only possible but also the only academically plausible option to foster.